Corrosion Protection of AISI 304 Stainless Steel with Melting Gel Coatings. (1st June 2016) - Aparicio, M.; Jitianu, A.; Rodriguez, G.; Degnah, A.; Al-Marzoki, K.; Mosa, J.; Klein, L.C.
Abstract: Methyl-substituted melting gels were used to coat AISI 304 stainless steel substrates. Crack-free coatings up to 1 mm in thickness were obtained. SEM micrographs of cross-sections confirm good adhesion to the surface. Samples were subjected to structural characterization using FT-IR, and Raman spectroscopy. Mechanical properties were investigated by micro-scratch tests. Electrochemical analyses (anodic polarization and electrochemical impedance spectroscopy) were performed in 3.5% NaCl solutions. Electrochemical tests show excellent performance of the coatings against corrosion with no sign of degradation after several months of immersion.